1984
DOI: 10.1007/bf01656040
|View full text |Cite
|
Sign up to set email alerts
|

Cholangitis

Abstract: Comparative study of the clinical features of 125 cases of acute cholangitis revealed that acute obstructive suppurative cholangitis (AOSC, 19 cases) was characterized by leukocytosis, high transaminase levels, bilirubinemia, and a marked thrombocytopenia. Most species of bacilli isolated from the purulent bile were gram‐negative and in 9 of 12 cases of AOSC that we checked, the same species were found in the blood as in the bile. In 12 of the 19 cases of AOSC, plasma endotoxin levels were assayed by theLimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 11 publications
(12 reference statements)
0
8
0
1
Order By: Relevance
“…Also, there was no significant difference between the bacterial virulence factors noted in the group with AC, compared with those noted in the control group, except for the papG class II allele. If the obstructed bile duct is untreated in patients with AC, the disease may progress with the development of shock or mental depression [13]. Lau et al [20] reported that endoscopic drainage is effective in lowering biliary pressure, aborting endotoxemia, and improving the clinical signs and symptoms of AC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there was no significant difference between the bacterial virulence factors noted in the group with AC, compared with those noted in the control group, except for the papG class II allele. If the obstructed bile duct is untreated in patients with AC, the disease may progress with the development of shock or mental depression [13]. Lau et al [20] reported that endoscopic drainage is effective in lowering biliary pressure, aborting endotoxemia, and improving the clinical signs and symptoms of AC.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli is the most commonly observed pathogen in studies of biliary bacteriology, on the basis of results of cultures of choledochal bile obtained from patients with or without AC or from patients with choledocholithiasis [7][8][9][10]. The incidence of bacteremia among patients with AC has varied from 0% to 75%, and E. coli has remained the pathogen most frequently associated with the disease [11][12][13][14][15]. Sakurai et al [16] found that adherence of E. coli to the epithelium of the human gallbladder correlated with the degree of epithelial damage.…”
mentioning
confidence: 99%
“…Cette forme grave est observée chez moins de 10 % des malades[58]. Le traitement de l'angiocholite grave repose sur une désob-struction en urgence des voies biliaires[59], en plus de méthodes de réanimation habituelle et de l'antibiothérapie. L'étude randomisée de Lai et al[58] a comparé le traitement chirurgical et le drainage endoscopique chez 82 malades ayant une angiocholite sévère définie par l'existence d'un choc septique ou la persistance d'un état septique malgré un traitement antibiotique adapté.…”
unclassified
“…There is now good evidence that endoscopic drainage is associated with less morbidity and mortality than urgent surgical intervention [26][27][28][29][30][31][32][33][34][35][36][37][38][39] (Table 3). Leese et al, 39 in a nonrandomized study, showed that early surgical de-compression was associated with a significantly higher 30-day mortality (6/28) than early endoscopic drainage (2/43), despite the latter group being older with more medical risk factors.…”
Section: Endoscopic Versus Surgical Drainagementioning
confidence: 99%